PENGARUH PERSEPSI PENGGUNAAN CHATBOT BERBASIS AI (ARTIFICIAL INTELLIGENCE) SEBAGAI VIRTUAL ASSISTANT GURU TERHADAP KUALITAS PEMBELAJARAN SD GUGUS V PENGASIH - Nasicha Qairo Riyani; Yulia Palupi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid development of Artificial Intelligence (AI) has encouraged the use of digital-based learning innovations, including chatbot technology as a virtual assistant for teachers. However, teachers’ perceptions of AI chatbot utilization and its impact on learning quality remain underexplored. This study aimed to examine the influence of teachers’ perceptions of AI‐based chatbots as virtual assistants on learning quality in SD Gugus V Pengasih in the academic year 2025/2026. This research employed a quantitative approach using a population study involving 41 elementary school teachers. Data were collected using questionnaires and analyzed through descriptive statistics and simple linear regression. The results indicated a significant influence between teachers' perceptions of AI chatbot utilization and learning quality. The regression test yielded a coefficient value of 0.498 with t (4.433) > t-table(2.021) and significance level of p = 0.000 < 0.05. Furthermore, the coefficient of determination (R²) of 0.335 showed that 33.5% of the variance in learning quality was explained by teachers’ perceptions of AI chatbot usage, while the remaining 66.5% was affected by other factors. These findings suggest that positive perceptions of AI chatbot utilization have the potential to improve teaching effectiveness and support interactive, adaptive, and efficient learning processes at the elementary school level.